Histopathological findings following pipeline embolization in a human cerebral aneurysm at the basilar tip. Issue 2 (April 2016) - Dai, Daying; Ding, Yong-Hong; Kelly, Michael; Kadirvel, Ramanathan; Kallmes, David
We report histopathological findings from a human cerebral aneurysm following treatment with a flow diverter. A 75-year-old male underwent flow diversion treatment (Pipeline Embolization Device (PED)) and coil embolization for treatment of an aneurysm at the basilar tip. At four months, angiography showed complete aneurysm occlusion; at 12 months angiography demonstrated that the aneurysm had reopened. The patient expired from brainstem compression. The aneurysm cavity was primarily filled with unorganized thrombus. Thick, interrupted neointima crossed the neck interface indicating blood flow into aneurysm through small channels. Along the parent artery the PED was covered by neointima having a measured thickness of 0.19 ± 0.01 mm; the maximal stenosis of the proximal parent artery was 27%. The perforating arteries that were crossed by the PED remained patent. Findings in this human case are similar to those in the elastase-induced aneurysms in rabbits.